2014
DOI: 10.1007/s00264-014-2343-9
|View full text |Cite
|
Sign up to set email alerts
|

Understanding bone safety zones during bone marrow aspiration from the iliac crest: the sector rule

Abstract: Using the sector system, trocars can be directed away from neural and vascular structures and toward zones that are likely to contain larger bone marrow stock.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
49
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(51 citation statements)
references
References 13 publications
1
49
0
1
Order By: Relevance
“…Aiming at achieving safe aspiration of the marrow, Hernigou et al [17] have developed the sector rule for BMA from the iliac crest, which he popularised as the concept of “safety zones”. They studied the anatomy of the iliac bone including the adjacent neurovascular elements that are susceptible to damage by the trocar when it is introduced into the iliac crest.…”
Section: Resultsmentioning
confidence: 99%
“…Aiming at achieving safe aspiration of the marrow, Hernigou et al [17] have developed the sector rule for BMA from the iliac crest, which he popularised as the concept of “safety zones”. They studied the anatomy of the iliac bone including the adjacent neurovascular elements that are susceptible to damage by the trocar when it is introduced into the iliac crest.…”
Section: Resultsmentioning
confidence: 99%
“…Representing the largest population of WBCs in the circulation, polymorphonuclear leukocytes (PMNs or granulocytes) constitute the first line of phagocytic defense. Due to the relatively short life span of PMNs, the bone marrow continuously produces these phagocytes from haematopietic precursors to maintain homeostatic levels of circulating PMNs [33,40]. The existence of circulating progenitor cells in the peripheral blood of man was first documented by McKredie et al in 1971 [31].…”
Section: Discussionmentioning
confidence: 99%
“…These haemopoietic stem cells also circulate in the peripheral blood of humans [33]. In humans the total number of circulating granulocyte-macrophage colony-forming units (CFU-GM) in the peripheral blood is one-tenth to one-fiftieth that of bone marrow [33], and normally increases in case of infection [33]. A factor limiting the control of bacterial infection may be the inability to obtain sufficient quantities of granulocytes and macrophages precursors in the peripheral blood due to bone marrow failure following a severe trauma.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Pierini et al analyzed MSC yield from the posterior or anterior iliac crest and the subchondral knee sites and concluded that the posterior iliac crest was preferable although no differences were found for viability, phenotype, expansion kinetics or multilineage differentiation (13). Hernigou studied the risk of complications when harvesting from the iliac crest and determined that higher risks such as trocar contact with the external iliac artery were observed with aspiration in the four most anterior sections with a higher risk in women (16). Placement of the trocar deeper than 6 cm in the posterior iliac crest was at risk for sciatic nerve and gluteal vessel damage.…”
Section: Harvesting and Characterization Of Msc From Different Tissuesmentioning
confidence: 99%